Inclusive Education for Children with Special Needs in the Digital Age - Endah Meilani Sari (Sekolah Tinggi Agama Islam Kuningan, 2025)
Inclusive education for children with special educational needs (SEN) in the digital era offers both unprecedented opportunities and complex challenges. Technological tools such as assistive technologies, adaptive learning platforms, and artificial intelligence can facilitate personalized instruction, enhance accessibility, and foster increased participation in heterogeneous classrooms. However, successful implementation demands more than mere technology acquisition. Key obstacles include insufficient teacher training in digital pedagogy, high costs and inequities in access to digital infrastructure, ethical concerns related to data privacy and algorithmic bias, and the risk of marginalizing children due to socio-economic disparities. This article investigates current practices and barriers in implementing inclusive education in digitally enabled environments. Through a systematic literature review of recent studies (2022-2025) and case analyses, it identifies: the most widely adopted technologies; the roles and competencies teachers require; policy and institutional conditions that facilitate implementation; and the unintended negative consequences when challenges are neglected. The findings suggest that integrative approaches combining technology, teacher professional development, inclusive curricula design, and supportive policy frameworks are crucial. It is also essential to incorporate stakeholder voices, particularly those of children, families, and special educators, in design and evaluation stages. The article concludes with recommendations for policy makers, practitioners, and researchers to ensure that digital inclusion does not remain a promise but becomes a sustainable practice that promotes equity, dignity, and quality of education for all learners.